Exploring the use of signals of opportunity for practical localization - Cheng, Chi (2015)
The Global Positioning System (GPS) provides position estimates on the Earth at anytime, anywhere and in any weather. However, to provide robust localization performance, GPS requires an unobstructed path to satellite signals. As such, GPS performance generally degrades or becomes non-existent in environments like indoors or in larger urban areas. So the use of non-localization purposed sig- nals, commonly referred as Signals of Opportunity (SOP) and including signals such as radio (AM/FM, DAB) transmission tower, cellular/mobile phone network (GSM/3G) base stations, LEO satellite signals (Iridium/Orbcomm), and Wi-Fi access points are being considered as alternatives for position estimation. Different signals have different signal structures, thus will be used at different ways. In this research, we will investigate properties of signals come from LEO Iridium satellites, GEO Inmarsat Satellite and airplanes. Specifically, we will ex- plore the usage of time difference of arrival (TDOA) techniques on those signals of opportunity. Moreover, we also propose an all-wireless relaying architecture for improving the performance of TDOA based localization . For this research, Universal Software Radio Peripherals (USRPs) are used for all experiments and implementations.